On The Maximum Leaf Number of a Family of Circulant Graphs - Muga, Felix P, II (Archīum Ateneo, 2014)
This paper determines the maximum leaf number and the connected domination number of some undirected and connected circulant networks which are optimal among all the maximum leaf numbers and connected domination numbers of circulant networks of the same order n and the same degree 2k. We shall tackle this problem by working on the largest possible number of vertices between two consecutive jump sizes.